(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction Community Health Workers (CHW) play a very important role in health promotion. Therefore, in order to strengthen the communities, it is imperative that CHWs be strengthened. This systematic review examined various interventions conducted in different parts of the world on the empowerment of CHWs. Methods In this study, after defining the research questions, search terms were determined and appropriate databases such as Web of Science, Scopus, PubMed, SID, Magiran, IranDoc, and Google Scholar were searched. After defining the inclusion and exclusion criteria and determining the scientific quality of the studies, appropriate articles were selected and finally the interventions to strengthen CHWs were summarized. Results We found 122 articles that addressed the empowerment of CHWs. After reviewing the articles, 13 of them were identified as related to the objectives of this study. The results show that old techniques such as lectures, seminars, and face-to-face meetings were used to empower CHWs, while a large number of researchers also used new tools such as the Internet, cell phones, and mobile applications to empower CHWs in various aspects. Conclusions This review of the various interventions to empower health workers shows that both old methods and new technologies are being used for this purpose. However, the use of information and communication technologies (ICTs) to strengthen the health workforce is growing rapidly. These findings can be useful for health policy managers, health care centers and research organization. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 950-956